Capturing on-farm realities with IMPACTLite - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
In the early 2000s, the International Livestock Research Institute (ILRI) started developing a tool to capture key factors of farming systems in standardized, quantitative data sets, ready to feed into models. Their product, the Integrated Modelling Platform for Mixed Animal-Crop Systems (IMPACT), included a comprehensive survey and a data collection software package.The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) recently backed an effort to streamline and update this tool, making it much quicker to implement and more useful for modelling and agricultural development studies. The new version, IMPACTlite, has now been rolled out at 13 CCAFS research sites in 12 countries, and other research programs are also starting to use IMPACTLite as a foundation for their own studies.